2019
DOI: 10.7196/samj.2019.v109i4.13565
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of melanoma in South Africa: An exploratory analysis of National Cancer Registry data from 2005 to 2013 with a specific focus on melanoma in black Africans

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…36,37 Similarly, data from the South African National Cancer Registry documented much higher melanoma incidence rate in white South Africans, 23.2 per 100,000, compared with 0.5 per 100,000 in blacks. 38 The 66 cases of melanoma in our study…”
Section: Discussionmentioning
confidence: 81%
“…36,37 Similarly, data from the South African National Cancer Registry documented much higher melanoma incidence rate in white South Africans, 23.2 per 100,000, compared with 0.5 per 100,000 in blacks. 38 The 66 cases of melanoma in our study…”
Section: Discussionmentioning
confidence: 81%
“…With regards to the demographics of subjects with a confirmed diagnosis of skin cancer it is not surprising that the majority of patients were identified as white patients, as this group will be most at risk of developing skin cancer [2,12] ( Table 2). e mean age for patients with confirmed skin cancer was 65.68 and in keeping with previous reports on age for MM and NMSC that showed people over the age of 60 to have a higher incidence of skin cancer [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…e number of MM cases in our study may even be underrepresented since a large percentage of MM are diagnosed in the private sector and possibly at primary care clinics and secondary hospitals without being referred to a tertiary hospital for biopsy. Tod et al found that 75% of all MM cases in South Africa are diagnosed in the private sector [12]. ere was only one case of MM diagnosed some authors consider KA as a precursor of SCC, a well-differentiated SCC or an abortive malignancy with invasive potential [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that thicker CM are associated with a significant cost escalation (ZAR 2931 (US$497) for lesions <1 mm thick, and ZAR 7149 (US$1213) for lesions >1 mm thick), providing an economic argument for screening at risk populations [12]. Most CMs in SA are diagnosed in the private sector [13]. Melanoma is considered by one of the largest private medical insurers to be amongst the top ten cancers by cost within the scheme, with an average cost per member of ZAR 60,926 (as at Jan-Dec 2017) [14].…”
Section: Costs Due To Skin Cancer In South Africamentioning
confidence: 99%